(untitled) (International Journal of Scientific Pediatrics, 2023)
Abstract:This article presents the results of a retrospective analysis of outpatient records of 60 children born with CHD during the pandemic. The frequency of occurrence and features of the clinical course of congenital heart defects have been established. Purpose of the study: To investigate the incidence and clinical course of CHD in children during the pandemic. Objectives of the study: 1. To study the incidence of CHD in children during the pandemic. 2. To analyze the peculiarities of the clinical course of CHD during the pandemic period. Materials and Methods. The work was performed at the Department of Pediatrics of BukhGMI and Bukhara City Maternity Complex. In a retrospective study of the history of newborn development for the period 2019-2020, 33 cases of newborns with CHD were identified. Newborns with CHD underwent the following methods of investigation: general clinical examination, clinical and laboratory (general blood count with unfolded lycoformula, blood coagulation, inflammatory markers - CRP, procalcitonin, interleukin-1 and 6, Ig m and G for sARs-Cov-2), instrumental (review chest X-ray, ECG, EchoCG) studies. Results and their discussion. Analysis of the history of neonatal development by gestation showed that births at 22-37 weeks accounted for 38%, at 38-42 weeks-50.0%, and at 42 and more weeks-12% of cases. Of 33 newborns with CHD, 18 (52.9%) had an interventricular septal defect. Atrial septal defect was diagnosed in 8 children (23.5%), and open ductus arteriosus was diagnosed in 8 children (23.5%), in 6 children (17.6%), combination of interventricular septal defect with open ductus arteriosus - in 1 child (2.9%), the smallest share among the detected malformations were: atrial septal defect in combination with pulmonary artery stenosis, isolated pulmonary artery stenosis, tetrada Fallo and aortic valve stenosis, which occurred in equal percentage - 0.3%. Conclusions: There is a high rate of acute carditis and pediatric inflammatory multisystem syndrome associated with CovID-19 among children with congenital heart disease after maternal CovID-19 during pregnancy.